Periodic Components of the Fatou Set in Angular Region - Gurung, Nirmal; Singh, Ajaya (Journal of Nepal Mathematical Society, 2022)
Here we discuss, for a given integer, the existence of transcendental entire function such that its number of periodic Fatou components lie in angular regions and their periodicity are related to the integer.